PRAKTIK BAHASA INGGRIS MENJADI TOUR GUIDE BAGI KARANG TARUNA DESA LUMBAN PEA TIMUR KABUPATEN TOBA - Elita Modesta Br. Sembiring; Martina Girsang; Charles D. M. Silalahi; Faido M. P. Simanjuntak; Himpun Panggabean; Nurhayati Purba; Karana Jaya Tarigan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
The Community service entitled “Praktik Bahasa Inggris menjadi Tour Guide di Desa Lumban Pea Timur, Kecamatan Balige Kabupaten Toba” is faced to serve the people especially Karang Taruna, the young community of the village. This community service was conducted on  8-11 June 2022. It exercises the Karang Taruna community to speak English in order to increase their ability in English as the young generation who lives in tourist destination. It is hoped to increase the economy by improving their quality in guiding tourism from local, national and international tourists. By using discussion, sharing ideas and practice English, the young people or Karang Taruna are trained to be good tour guides.